Treatment Outcomes of a Shortened Secure Residential Stay Combined With Multisystemic Therapy: a Pilot Study - Rovers, Anne (International journal of offender therapy and comparative criminology, 2019)
ThuisBest is a newly developed family focused treatment that combines secure residential youth care with multisystemic therapy (MST), allowing adolescents to return home after secure residential youth care more quickly. The purpose of this pilot study was to examine treatment outcomes for adolescents in ThuisBest (n = 86, Mage = 15.2 years, 63% boys) and to what degree those treatment outcomes could be predicted by client characteristics. The results showed that externalizing behavior problems and parenting stress had decreased at the end of treatment. After ThuisBest, 83% of the adolescents did not have new police contact, 72% lived at home, and 89% attended school or work. Almost none of the treatment outcomes could be predicted by any of the client characteristics. ThuisBest seems a promising trajectory, as it reduces the length of the stay in secure residential youth care, and may, therefore, be more cost-effective than standard secure residential youth care. However, given the lack of a control-group and follow-up data, findings must be interpreted as preliminary.